1986
DOI: 10.1118/1.595852
|View full text |Cite
|
Sign up to set email alerts
|

Consideration of physical parameters to predict thermal necrosis in acrylic cement implants at the site of giant cell tumors of bone

Abstract: In the previous paper we had developed a general thermodynamic equation describing a polymethylmethacrylate implant at the site of giant cell tumors. In this paper we consider various characteristics of bone and methylmethacrylate crucial to the analysis such as thermal conductivity, specific heat, density, and heat generation. Also, an estimation of the temperature at which adjacent cells die is analyzed from literature. Finally, using the physical constants measured in laboratory situations a temperature pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
5

Year Published

1988
1988
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 0 publications
1
15
0
5
Order By: Relevance
“…Although little experimentation has been done to determine thermal conductivity, specific heat, heat capacity, and heat of fusion for ionomeric cements, those values reported to date have been significantly lower than those for cortical and cancellous bone [19]. The histological character of tissue interaction with the Ho1mium:YAGlaser in the power setting as described in the freerunning mode is similar to that of the Holmium: YAG-lasers in the Q-switched mode, assessed in former studies of our study group [7,201.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Although little experimentation has been done to determine thermal conductivity, specific heat, heat capacity, and heat of fusion for ionomeric cements, those values reported to date have been significantly lower than those for cortical and cancellous bone [19]. The histological character of tissue interaction with the Ho1mium:YAGlaser in the power setting as described in the freerunning mode is similar to that of the Holmium: YAG-lasers in the Q-switched mode, assessed in former studies of our study group [7,201.…”
Section: Discussionmentioning
confidence: 78%
“…In addition, every single laser shot caused soiling of the optic whether irrigation was used or not, which renders proper surgical proceedings impossible. Similar to the mechanism of bone ablation proposed by On the basis of studies with polymethylmetacrylate [19], molten filling material as identified by endoscopic examination (Fig. lc) can therefore be explained by the specific chemical and physical characteristics of ionomeric cement.…”
Section: Discussionmentioning
confidence: 92%
“…Although little experimentation has been done to determine the thermal conductivity, specific heat, heat capacity, and heat of fusion for methacrylate, those values that have been reported are significantly lower than those for the cortical and cancellous bone typically found in the rabbit femur [9]. Extrapolation of these physical constants to our system does involve some uncertainties, but these parameters could be useful in developing a temperature profile that could facilitate prediction of the zone of thermal damage in both bone and methacrylate.…”
Section: Discussionmentioning
confidence: 91%
“…The most likely explanation for bone or turnout necrosis following the introduction of cement is thermal injury. The thermal threshold for bone necrosis ranges in different studies from 48°C to 70°C [10,19,21]. However, it is generally accepted that bone necrosis does not occur when the temperature is below 48°C and between 48°C and 60°C the occurrence of bone necrosis is time dependent.…”
Section: Discussionmentioning
confidence: 99%